Kidnapped - MacLaughlin, Don (Radio actor); Kramer, Mandel; WOR Collection (Library of Congress) (London: Macmilla, 1956)
Crime, mystery show with U.S. Government counterspy David Harding.
Production level cataloging.
Written by Phillips H. Lord.
Broadcast Oct. 20, 1946, 5:30-6:00 pm.
Playback copy.
Preservation master.
Keywords: Adventure radio programs; Crime or mystery programs -- Radio